IMPROVING STUDENTS’ NARRATIVE WRITING ABILITY BY IMPLEMENTING DIGITAL PICTURE SERIES IN ONLINE EFL CLASS - Girsang, Evani Risa (RETAIN, 2022)
Writing skill is considered as one of the most difficult skill to be learnt as it is an active productive skill. Students have to learn how to find out ideas and pour it into a certain type of writing product. In narrative writing, students have some difficulties to find idea and to organize the narrative text. Many studies have been conducted to figure out the ways in helping students improve their narrative writing ability. Picture series is one of many proven ways to help students improve their narrative writing. This study emphasized the use of digital narrative writing because during this research was being conducted, classes are conducted online due to Covid19 pandemic. Researcher used a web-side based application called StoryBoardThat.com as the media of digital picture series. This study is to prove that the implementation of digital picture series can improve students’ narrative writing ability and also to see students’ response of it. This research is done to 15 students of X MIPA 1 grader in Sekolah Citra Berkat, Surabaya. Researcher used two instruments to find out the data of this study. To find out whether digital picture series can improve students’ narrative writing, writer used pre-experimental research which took students’ pre-test and post-test result and processed using Paired Sample T-test to see the improvement of the narrative writing. Then to determine students’ response towards the implementation of digital picture series, researcher used questionnaire in a form of five-points Likert Scale consist of 21 statements which grouped into 7 topics, which each of the topic consisted of 3 statements. The result of this study showed a significant improvement of students’ narrative writing (2-Tailed) < 0.05 (Ha). From the questionnaire it can be seen that 80% students agreed that digital picture series implementation is more fun. Based on the result, it can be concluded that digital picture series implementation can improve students’ ability in narrative writing. Keywords: digital picture series, narrative writing